2001
DOI: 10.1002/bit.1044
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mass‐transfer phenomena in anaerobic granular sludge

Abstract: The kinetic properties of acetate-degrading methanogenic granular sludge of different mean diameters were assessed at different up-flow velocities (V(up)). Using this approach, the influence of internal and external mass transfer could be estimated. First, the apparent Monod constant (K(S)) for each data set was calculated by means of a curve-fitting procedure. The experimental results revealed that variations in the V(up) did not affect the apparent K(S)-value, indicating that external mass-transport resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 29 publications
(28 reference statements)
1
50
0
1
Order By: Relevance
“…These changes could not be compensated for in the long term by the use of chemical buffer solutions. The use of a trace element solution according to Gonzalez-Gil et al [25] allowed stable digestion at a low loading of 2 g VS L -1 day -1 but the recommended dose may have been insufficient to satisfy trace element requirements when higher loadings were applied. The formulation was also shown to be deficient in tungsten and supplementation with this element was required even at low OLR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These changes could not be compensated for in the long term by the use of chemical buffer solutions. The use of a trace element solution according to Gonzalez-Gil et al [25] allowed stable digestion at a low loading of 2 g VS L -1 day -1 but the recommended dose may have been insufficient to satisfy trace element requirements when higher loadings were applied. The formulation was also shown to be deficient in tungsten and supplementation with this element was required even at low OLR.…”
Section: Discussionmentioning
confidence: 99%
“…In the 4-liter trial the TE solution proposed by Gonzalez-Gil et al [25] was added at the start of the experiment to each digester in the proportion of 1 mL L -1 , and then weekly in the same proportion based on the volume of feedstock added. In the 1.…”
Section: Digester Feed and Supplementsmentioning
confidence: 99%
See 2 more Smart Citations
“…transfer of substrate from the bulb liquid to the particle surface) is of minor relevance for the removal of substrate. Similarly, Gonzalez-Gil et al (2001) studied the influence of internal and external mass transfer in the Monod model and concluded that external mass transfer can normally be neglected. Consequently, Eq.…”
Section: Governing Equationsmentioning
confidence: 99%